2017
DOI: 10.1515/cee-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Airborne Sound Insulation of a Straw Bale Partition Wall

Abstract: This paper describes the results of a scientific project focused on determining of the Airborne Sound Insulation of a peripheral non-load bearing wall made of straw bales expressed by Weighted Sound Reduction Index. Weighted Sound Reduction Index was determined by measuring in the certified acoustic laboratory at the Faculty of Mechanical Engineering at Brno University of Technology. The measured structure of the straw wall was modified in combinations with various materials, so the results include a wide rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In general, the airborne sound insulation performance of a straw bale wall depends on the finishing such as plaster, acoustic board, etc. as reported in Teslik et al [88] and Marques et al [14], and less influenced by the straw bale itself which are typically protected within the finishing. The field tests on the straw bale buildings showed a mixed results, but in general poor performance was observed by Dance and Herwin [90], Cascone et al [18], and D'Alessandro et al [19], even if studies from Deverell et al [89] and Wall et al [66] showed a satisfactory result.…”
Section: Sound Insulation Performancementioning
confidence: 72%
See 2 more Smart Citations
“…In general, the airborne sound insulation performance of a straw bale wall depends on the finishing such as plaster, acoustic board, etc. as reported in Teslik et al [88] and Marques et al [14], and less influenced by the straw bale itself which are typically protected within the finishing. The field tests on the straw bale buildings showed a mixed results, but in general poor performance was observed by Dance and Herwin [90], Cascone et al [18], and D'Alessandro et al [19], even if studies from Deverell et al [89] and Wall et al [66] showed a satisfactory result.…”
Section: Sound Insulation Performancementioning
confidence: 72%
“…Fig. 15 shows the laboratory testing on airborne sound insulation of straw bale wall prototype according to ISO 10140-2 [14,66,88]. Fig.…”
Section: Sound Insulation Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Although traditional clay building materials, such as adobe bricks, clay blocks, and blocks, as well as newly developed compact floor blocks, have been used successfully in various projects, more and more interest has been shown in the use of unrefused clay bricks produced in large size brick manufacturers industries. Teslík, J. et al [26], studied the effect of adding straw bales to the peripheral non-load-bearing wall. The straw wall was remodeled in combinations with various materials which included; without plasters, with a wet clay plaster from one side, with dry clay plaster from one side, and with a double-sided clay plaster.…”
mentioning
confidence: 99%
“…Their porous structure motivated eco-builders for the exploitation of natural lignocellulose sources and recyclable bio-waste as filler constituents into green composites, and in the design and development of new bio-based materials with fascinating ability to regulate the indoor moisture level and to ensure better indoor air quality [1]. Bio-aggregate-based composite are also providing good insulation properties [2]. There is a large group of fast renewable vegetal-origin materials, of which great importance to technical hemp is attached.…”
mentioning
confidence: 99%